Alternative Work Arrangements, Work Environment, and Job Stress on Job Satisfaction and Turnover Intention - Mawardi, Moh. Cholid (Golden Ratio of Human Resource Management, 2022)
This study was conducted to analyze the influence of Alternative work arrangementss, work environment, and job stress on job satisfaction. The object of this research is millenial bankir with a total sample of 120 employees and data collection use online survey. Data were analyzed using Structural Equation Modeling (SEM) with AMOS. The results of this study indicate that Alternative work arrangementss, job stress have a negative significant effect on job satisfaction, work environment has a positive significant effect on job satisfaction, job satisfaction has a positive significant effect on turnover intention, and Alternative work arrangementss have a positive effect and significant on turnover intention, the work environment has a negative and significant effect on turnover intention, work stress has a positive insignificant effect on turnover intention, Alternative work arrangementss have a negative significant effect on turnover intention through job satisfaction, the work environment has a positive significant effect on turnover intention through job satisfaction, and job stress has a negative significant effect on turnover intention through job satisfaction. The human resource management must implement the suitability of employee competencies with their field of work better so that it is expected to reduce turnover in employees creating a conducive work environment.